16 Chronotropic and dromotropic responses to exercise in heart failure with preserved ejection fraction (hfpef) patients and controls. (5th June 2017) - Lodge, Freya; Erdei, Tamas; Edwards, Heather; Yousef, Zaheer; Fraser, Alan
Abstract : Introduction: The hallmark of Heart Failure with Preserved Ejection Fraction (HFpEF) is exercise intolerance. The mechanisms for this are numerous, but chronotropic incompetence, defined as a failure to reach at least 70% of the age-predicted maximum heart rate (HR) on maximal exercise, has been reported to contribute. Impaired Heart Rate Reserve, a measure of HR achieved on maximal exercise compared with age-predicted maximum heart rate, is correlated with negative cardiovascular outcomes. In normal subjects, the PR interval shortens during exercise as parasympathetic tone reduces. This is known as dromotropy and is reduced in subjects with coronary artery disease. We formed the hypothesis that HFpEF patients may also have impaired PR shortening and that this may contribute to exercise intolerance. Methods and results: HFpEF patients and controls (healthy (H), hypertensive (HT) and breathless controls (BC)) from the MEDIA (Metabolic Road to Diastolic Heart Failure, EU FP7) trial at our centre underwent maximal semi-supine bicycle stress tests whilst on standard treatment. Electrocardiograms were examined by a single, blinded investigator for PR-interval and heart rate (HR) at: rest; submaximal exercise (HR 100 min-1); peak exercise; and 2 and 5 min after exercise. 110 subjects were recruited, of whom 24 were excluded (unable to exercise/atrial arrhythmia). Data on 86 subjects were analysed. Baseline characteristics are given in the Table. Resting HR was similar between groups, but maximal HR was lower in patients than all controls (p<0.05), as was HR (p<0.0001) (figure 1). HR recovery was impaired in patients versus healthy controls at 2 min (H=−34.8, p<0.001) and 5 min (H=−17.9, p=0.04) of recovery. PR interval decreased across all groups from rest to peak (mean −7.2%, p=0.025). PR interval was similar at rest; it shortened less in patients (5.2%) versus healthy controls (11.4%), but not when corrected for difference in peak HR. PR/HR did not vary by group at any stage. Beta blockers did not affect PR interval, but reduced HR and HR at all stages (35% reduction from rest to peak) (figure 2). The difference in maximal HR between patients and controls persisted after excluding beta blocked subjects. Patients were 13% older than controls (p<0.01). Subjects from all groups of less than 70 years had significantly increased PR shortening (mean difference −9.1 ms, p=0.02) and change in HR (mean difference 15.7 ms, p<0.001) between rest and peak than those over 70 years. Patients had significantly higher Body Mass Indices (BMI) than hypertensive or healthy subjects (H=−3.6, p=0.02, H=−3.5, p=0.003 respectively), as did breathless controls (H=3.1, p=0.012, H=2.8, p=0.027). Conclusions: Patients with HFpEF have chronotropic incompetence and impaired HR recovery, but there was no evidence of dromotropic incompetence in this study.